Hybird PV-Wind System with Data Aquisation and Storage System - Ojo, Oluwafemi Tayo (Mikailalsys Journal of Advanced Engineering International, 2025)
This project, conducted at the Department of Electrical Engineering, Ahmadu Bello University, Zaria, focuses on the design, hybridization, and analysis of an islanded microgrid system. The study begins with an evaluation of the performance of an existing standalone solar (PV) system. It then explores the integration of a wind energy system to form a hybrid energy system, enhancing reliability and efficiency. A key component of this project is the integration of a data acquisition system for real-time monitoring of weather conditions, including solar irradiance, wind speed, temperature, and humidity, alongside load profiling. Additionally, a data storage system is implemented to facilitate future referencing and analysis. This comprehensive approach aims to optimize the hybrid microgrid's performance, ensuring a stable and sustainable energy supply in off-grid settings.